Morphology and scaling of compound eyes in the smallest beetles (Coleoptera: Ptiliidae). (January 2019) - Makarova, Anastasia A.; Meyer-Rochow, V. Benno; Polilov, Alexey A.
Abstract: The coleopteran family Ptiliidae (featherwing beetles) includes some of the smallest insects known with most of the representatives of this family measuring less than 1 mm in body length. A small body size largely determines the morphology, physiology, and biology of an organism and affects the organization of complex sense organs. Information on the organization of the compound eyes of Ptiliidae is scarce. Using scanning electron microscopy we analyzed the eyes of representatives of all subfamilies and tribes and provide a detailed description of the eye ultrastructure of four species ( Nephanes titan, Porophila mystacea, Nanosella sp. and Acrotrichis grandicollis ) using transmission electron microscopy. The results are compared with available data on larger species of related groups of Staphyliniformia and scale quantitative analyses are performed. The eyes of Ptiliidae consist of 15–50 ommatidia 6–13 μm in diameter and all conform to the apposition acone type of eye with fused rhabdoms of banded organization. Each ommatidium has the typical cellular arrangement present also in the eyes of larger staphyliniform beetles, but strongly curved lenses, short cones, reduced pigment cells, a high density of pigment granules and certain modifications of the rhabdom seem typical of ptiliid eyes. Allometric analyses show that as body size decreases, the number of facets drops more steeply than their average size does. Graphical abstract: Image 1 Highlights: Decrease in body size is accompanied by reduction of the number of facets in the compound eyes. Reduction in facet diameter begins only after reaching a certain minimum number of ommatidia. The compound eyes of Ptiliidae are of the apposition type with acone crystalline cones and a fused banded rhabdoms. Miniaturization in insect eyes manifests itself in increased convexity of the lense and greater interommatidial angle. The minute eyes possess a high density of pigment grains and a general compaction of the elements within ommatidia.